2012
DOI: 10.1136/jmedgenet-2012-100826
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage and copy number variation analysis reveals 710 kb duplication on chromosome 1p31.3 responsible for autosomal dominant omphalocele

Abstract: Background Omphalocele is a congenital birth defect characterised by the presence of internal organs located outside of the ventral abdominal wall. The purpose of this study was to identify the underlying genetic mechanisms of a large autosomal dominant Caucasian family with omphalocele. Methods and findings A genetic linkage study was conducted in a large family with an autosomal dominant transmission of an omphalocele using a genome-wide single nucleotide polymorphism (SNP) array. The analysis revealed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Recently, Long et al [ 12 ] published a study suggesting a copy number variation (CNV) on SSC14 to be involved in development of umbilical hernia in pig. Also in humans some studies have been done on structural variations like deletions and duplications, suggesting that such variations also could play a role in occurrence of umbilical hernia [ 13 15 ]. Additionally, two studies in other species suggest that umbilical hernia is associated with the function of cyclin-dependent kinase inhibitory protein p57 KIP2 , a regulator of cell proliferation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Long et al [ 12 ] published a study suggesting a copy number variation (CNV) on SSC14 to be involved in development of umbilical hernia in pig. Also in humans some studies have been done on structural variations like deletions and duplications, suggesting that such variations also could play a role in occurrence of umbilical hernia [ 13 15 ]. Additionally, two studies in other species suggest that umbilical hernia is associated with the function of cyclin-dependent kinase inhibitory protein p57 KIP2 , a regulator of cell proliferation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only one genetic link in nonsyndromic and single defect cases has been studied. The particular genetic linkage analysis of a single family with a high incidence of nonsyndromic OMP showed a 710 kb duplication on chromosome 1p31.3 present on all OMP phenotypes (Radhakrishna et al, ). Other genes involve multiple malformations, with OMP as one of the genetic consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Approximatively 14% of all cases of omphalocele can be classified as isolated [ 2 ]. Despite several studies investigating the genetic causes [ 22 25 ] or environmental risk factors [ 24 ] involved in this malformation, the etiology of isolated omphalocele has not been fully elucidated. Kanagawa et al [ 23 ] described an extensive family with vertical transmission of isolated omphalocele, with nine subjects over three generations affected, suggesting an autosomal dominant pattern of inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these observations, inherited alterations have never been identified in these families. More recently, a genomic duplication was found in a large pedigree with autosomal dominant transmission of isolated omphalocele [ 22 ]. Genetic analysis revealed that all affected individuals were positive for a duplication at chromosome 1p31.3, suggesting the involvement of one or more genes in the duplicated region, including FOXD3 , ALG6 , ITGB3BP , KIAA1799 , DLEU2L , PGM1 , and the proximal portion of ROR1 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%